Theoretical Approaches in Bioarchaeology - Cheverko, Colleen M.; Prince-Buitenhuys, Julia R.; Hubbe, Mark (London ; New York : Routledge/Taylor & Francis Group, 2020)
"Theoretical Approaches in Bioarchaeology emphasizes how several different theoretical perspectives can be used to reconstruct the biocultural experiences of humans in the past. Over the past few decades, bioarchaeology has been transformed through methodological revisions, technological advances, and the inclusion of external theoretical frameworks from the social and natural sciences. These interdisciplinary perspectives became the backbone of bioarchaeology and strengthened the discipline's ability to address questions about past biological and social dynamics. Consequently, how, why, and when to apply external theory to studies of past populations are central and timely questions tied to future developments of the discipline. This book facilitates ongoing dialogues about theoretical applications within the field and interdisciplinary connections between bioarchaeology, biological anthropology, and other disciplines. Each chapter highlights how a theoretical framework originating from a social or natural science connects to past and future bioarchaeological research. For scholars and archaeologists interested in the theoretical applications of bioarchaeology, this book will be an excellent resource"--
Foreword; Chapter 1 - Theory in Bioarchaeology: An Introduction; Chapter 2 - Embodying Bioarchaeology: Theory and Practice; Chapter 3 - Gender; Chapter 4 - Bioarchaeological Applications of Intersectionality; Chapter 5 - Life Course Approaches and Life History Theory: Synergistic Perspectives for Bioarchaeology; Chapter 6 - Reconstructing Immune Competence in Skeletal Samples: A Theoretical and Methodological Approach; Chapter 7 - Niche Construction Theory in Bioarchaeology; Chapter 8 - Live Through This: Developing a Sustainable Pathway for Resilience Theory in Bioarchaeological Research; Chapter 9 - Structural Violence and Political Economy: Epistemological Considerations for Bioarchaeology; Chapter 10 - Making Silenced Voices Speak: Restoring Neglected and Ignored Identities in Anatomical Collections; Chapter 11 - Theoretical Approaches to Bioarchaeology: The View from Across the Pond; Chapter 12 - Towards a Bioarchaeology beyond Nature and Culture: Potentials and Possibilities in Contemporary Theoretical Bioarchaeology
OCLC-licensed vendor bibliographic record.
Keywords: Human remains (Archaeology); Archaeology -- Philosophy; Social archaeology; Paleoanthropology; SOCIAL SCIENCE / Archaeology; Bioarchaeology